Acoustic power of radiation of a circular plate fixed on the rim and vibrating under external pressure - RDZANEK, W. (Archives of Acoustics, 1992)
The main scientific aim of our work was the realization of theoretical research on the problem of energy radiation of axially-symmetric forced vibrations of a circular plate. This research focussed on the determination of frequency characteristics of relative acoustic power. A thin plate, fixed on the rim in a rigid and flat acoustic baffle, radiating into a lossless and homogeneous fluid medium was considered. Dynamic interactions between the acoustic wave radiated by the plate and the form of the radiations as well as losses in the plate were neglected. The active acoustic power of radiation was expressed with a single integral within finite limits and with elementary form in special cases, i.e., for high-frequency wave radiation and when the plate’s thickness is sufficiently small in relation to its diameter. The results of calculations are also presented in graphical form.